Libra – A Differentiated View on Facebook's Virtual Currency Project - Volker Brühl (Intereconomics, 2020)
Libra – a global virtual currency project initiated by Facebook – has been the subject of many controversial discussions since its announcement in June 2019. This paper provides a differentiated view on Libra, recognising that different development scenarios of Libra are conceivable. Libra could serve purely as an alternative payment system in combination with a dedicated payment token, the Libra coin. Alternatively, the Libra project could develop into a broader financial infrastructure for advanced financial services such as savings and loan products operating on the Libra Blockchain. Based on a comparison of the Libra architecture with other cryptocurrencies, the opportunities and challenges for the development of the respective Libra ecosystems are investigated from a commercial, regulatory and monetary policy perspective.
Keywords: 330